STRATEGY AND POLICY IN ILLEGAL TRADE IN BORDER OF EAST KALIMANTAN-MALAYSIA AND THE IMPLICATIONS FOR AEC 2015 - Asri, Syachrumsyah (Jurnal Aplikasi Manajemen, 2017)
Enforcement of the ASEAN free market in the AEC since 2015 provides opportunities and threats for the border region of East Kalimantan - Kaltara as the front porch of the strategic state. This study aims to determine the factors that cause the occurrence of illegal trade in the border region with Malaysia and the implications for AEC 2015. By using descriptive analysis method is a method that makes a picture in a systematic, factual and accurate information on the facts and seeking to explain how a problem occurs. This study shows that the circulation of goods Malaysia continues to increase and largely through the illegal trade. The illegal trade also occurs in agricultural products and forest products traded as raw materials, the price is cheap and the level of price elasticity to income is low and negative, while the illegal products from the Malaysian trade in processed products from an illegal trade which has contains valueadded and the resale value is relatively more expensive. The results of this study recommend strategies and policies that can be taken in controlling illegal trade in the border region of East Kalimantan-Malaysia as well as to support the AEC 2015 is through two aspects: 1) the strengthening of the law enforcement aspect (infrastructure, personnel, control mechanisms, co-operation), 2) economic development through: a) access to the distribution of public goods and services in the border region, especially items that are not economical in production on a local scale, b) development of industrial capacity based on local resources to meet the local needs, regional and capture global opportunities, c) strategy (a) and (b) achieved through the development of infrastructure capacity (physical and non-physical), investments, partnerships and alliances vertical and horizontal.